2014
DOI: 10.1519/jsc.0000000000000538
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Relative Distribution of Kettlebell Snatch Force-Time Characteristics

Abstract: The aim of this study was to compare mechanical output from kettlebell snatch and 2-handed kettlebell swing exercise. Twenty-two men performed 3 sets of 8 kettlebell snatch and 2-handed swing exercise with a 24 kg kettlebell on a force platform. Vertical and horizontal net impulse, mean force, displacement, the magnitude and rate of work vertical CM displacement was significantly larger than horizontal CM displacement, regardless of exercise (20±3 vs. 7±1 cm, p<0.0001); 2) the magnitude (253±73 vs. 3±1 J, p<0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 15 publications
4
36
1
Order By: Relevance
“…However, this is not always how power is used or computed in the literature. Specifically, sports biomechanists often split power into its 'components', as though it were a vector quantity; for example, reporting 'vertical' or 'horizontal' power (e.g., [47,48,49,50]). In a strict mechanical sense, these quantities are not real powers.…”
Section: Directional Powermentioning
confidence: 99%
“…However, this is not always how power is used or computed in the literature. Specifically, sports biomechanists often split power into its 'components', as though it were a vector quantity; for example, reporting 'vertical' or 'horizontal' power (e.g., [47,48,49,50]). In a strict mechanical sense, these quantities are not real powers.…”
Section: Directional Powermentioning
confidence: 99%
“…To date, the barbell snatch has received much attention and reviews of the literature have demonstrated it to be an effective exercise for strength and power development (Escamilla, Lander & Garhammer, 2000; Garhammer, 1993). In contrast, the kettlebell snatch has only just started to receive research attention (Falatic et al, 2015; Lake, Hetzler & Lauder, 2014; McGill & Marshall, 2012; Ross et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…The only study to date recorded the bilateral ground reaction force (GRF) of the kettlebell swing and snatch (Lake, Hetzler & Lauder, 2014). The kettlebell snatch and two-handed swing were analysed over three sets of eight repetitions performed with the intention of achieving the maximum velocity possible, with horizontal and vertical work, impulse, mean force and power of the kettlebell snatch and swing calculated (Lake, Hetzler & Lauder, 2014). Both exercises had greater vertical impulse, work and mean force power than the horizontal equivalent regardless of phase (Lake, Hetzler & Lauder, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…56 2014), The kettlebell snatch and two handed swing were analysed over three sets of eight 57 maximum repetitions, with horizontal and vertical work, impulse, mean force and power of the 58 kettlebell snatch and swing calculated (Lake et al 2014). Both exercises had greater vertical 59 impulse, work, and mean force power than the horizontal equivalent regardless of phase (Lake et 60 al.…”
mentioning
confidence: 99%